42 Deposited dose measurement using bremsstrahlung X-rays. (December 2018) - Ralite, F.; Koumeir, C.; Haddad, F.; Metivier, V.; Servagent, N.; Varmenot, N.
Abstract : Introduction: With the development of particle therapy, patient dose verification tools are needed to ensure the accuracy of treatment. Non-invasive methods to measure the deposited energy exist. These are based on the PET-imaging technique, taking advantage of the radionuclides created during the interaction of hadrons with the medium[1] . An alternative method is studied and presented in this work. The detection of bremsstrahlung X-rays (XR) emitted directly by medium[2] is a promising way to obtain all or part of the deposited energy in the medium. This study describes a method to determine the deposited dose by a charged particle beam, for different incident energies. The results obtained for protons and alpha particles of 70 MeV will be presented. Methods: The experimental set-up allows the irradiations of a PMMA target by alpha particles or protons delivered by the cyclotron ARRONAX (energy <70). The detection of bremsstrahlung X-rays is performed with a silicon detector. A theoretical model that takes into account the different contributions of bremsstrahlung[3] has been developed to model the emitted XR spectrum. Results: The first experiment, with alpha particles of 68 MeV, shows a good agreement between theoretical and simulated XR spectrums. The number of bremsstrahlung XR detected for one gray received by the medium is 1060+/−140. Uncertainty includes detection efficiency, the beam charge and the statistical counting fluctuations, and uncertainties about measurement of the number of the incident particles. The simulated spectrum indicates a number of 970 XR/Gy. Thus the number of XR per gray demonstrates a good sensibility. These encouraging results led us to perform experiments using proton beams with different energies. The analyses are in progress and the results will also be presented. Conclusions: This work presents an alternative, on-line, non-invasive method based on the measurement of bremsstrahlung XR emitted during the interaction of a particle beam with matter. Proof of concept was obtained for 68 MeV alpha particles. Proton beams with energies from 17 to 70 MeV are under study. The objective is to evaluate the sensitivity of the method, in order to use the bremsstrahlung to monitor the beam and/or the deposited dose at energies close to those used in protontherapy and hadrontherapy.